HYDROCARBON POTENTIAL OF TOLO BAY MOROWALI REGENCY: QUALITATIVE ANALYSIS - Suliantara Suliantara; Tri Muji Susantoro (Scientific Contributions Oil and Gas, 2015)
Tolo Bay is located between East Arm and Southeast Arm Sulawesi, reaching a water depth of up to 3500 meters below sea level. Regionally, this block is situated within Banggai Basin where some gas and oil fi elds are already in production. The closest fi eld is Tiaka Oil Field located about 125 kilometers northwest of the study area. A geo-science review has been conducted to clarify the potential existence of hydrocarbon in this block. Based on previous reports, papers, and subsurface data from the Directorate General of Oil and Gas, the study area is located within the collision area between Banggai-Sula Microcontinent and Sulawesi. This collision occurred during Late Creataceous and Middle Miocene periods. During drifting phase a sedimentation process occurred at the front of the Banggai-Sula Microcontinent. This sediment is potentially source rock and reservoir rock. Meanwhile, during the drifting phase the study area is interpreted as located at the southern part of Banggai-Sula Microcontinent. This different tectonic setting will impact on the type of sedimentary rock, hence source rock and reservoir rock occurrence in the study area is still unclear. As source rock and reservoir rock within the study area are unclear, hydrocarbon explorations will be very risky. In order to reduce exploration risk, it is proposed to conduct geological and geophysical studies using the latest seismic data that was surveyed by PT. TGS – NOPEC and PT. ECI – PGS.